The role of routine imaging in pediatric cutaneous melanoma. Issue 12 (19th August 2018) - Halalsheh, Hadeel; Kaste, Sue C.; Navid, Fariba; Bahrami, Armita; Shulkin, Barry L.; Rao, Bhaskar; Kunkel, Michelle; Artz, Nathan; Pappo, Alberto
Abstract: Background: Optimal imaging for children with pediatric malignant melanoma (MM) is unknown. Methods: We reviewed clinical and imaging findings of patients with American Joint Commission on Cancer (AJCC) stage IIC‐IV MM treated on our institutional MEL06 trial. All patients had baseline brain magnetic resonance imaging/computed tomography (MRI/CT), positron emission tomography/computed tomography (PET/CT), CT chest, abdomen, and pelvis (CTCAP). Patients on stratum A (PEG‐interferon, where PEG is pegylated; AJCC IIC, IIIA, IIIB; n  = 16) had imaging every 6 months; stratum B1 (PEG‐interferon and temozolomide; unresectable measurable disease, metastatic, or recurrent; n  = 2) had PET/CT scans every 2 months and brain imaging studies every 4 months; stratum B2 patients (PEG‐interferon and temozolomide; unresectable nonmeasurable, metastatic, or recurrent, n  = 3) had imaging every 4 months. Off‐therapy imaging was done every 6 months for 3 years. Results: There were 21 patients (11 females, 11 spitzoid, median age 14 years, head/neck [6], trunk [7], extremities [8]). Patients with spitzoid melanoma underwent 236 imaging studies in total (86 PET/CT, 81 CTCAP, 11 CT chest, 10 CT brain, 48 MRI brain) at a median cost per patient of $32, 718. Thirteen studies (5.8%) had findings that led to two biopsies (one positive). For conventional MM, 162 studies (61 PET/CT, 57 CTCAP, 8 CT chest, 7 CT brain, and 29 MRI brain) were performed with a median cost per patient of $23, 420. Twenty (14%) had findings leading to six biopsies (four positive). At 6.3 years (range 0.4‐9.2), 17 patients remain disease‐free. Conclusion: Children with spitzoid melanoma require minimal imaging at diagnosis and follow‐up. Patients with conventional MM should be imaged according to adult guidelines.